Modelling and simulation of adsorption process for removal of CO2 from natural gas in an offshore platform - Maalim, Kauthar Yussuf (2019)
The presence of CO2 in natural gas causes pipeline corrosion and increases operating costs during transfer from the offshore production platforms to the storage terminal. Due to space limitation and harsh operating environment, a robust and compact process such as pressure swing adsorption is preferable. To facilitate the study of process dynamics, simulation studies based on a derived mathematical model on a MATLAB software is presented. The effect of design parameters, focusing on the column height is considered, and it is found that for a typical laboratory scaled apparatus having diameter of 0.5 m. The maximum height required to adsorb 99 % CO2 is 3 m when the feed flow rate is fixed at 2.5 m3/s. The size of adsorbent particles is also impacting separation efficiency, and the optimum particle radius is found to be 1.25x10-3 m and the bed porosity was 0.2. Sensitivity analyses on the main operating parameters are also investigated. It is found that the initial CO2 feed composition has positive relationship to the adsorption efficiency. The 0.4 mole fraction was found to have sufficient separation efficiency of 90 %. The model is also tested for representing a typical industrial operation with 120 mmscfd. In this case, for a 4 m diameter column, a column height of 20 m is required. This is achieved with a 4 bed PSA system at a flow rate of 10.05 m3/s for each, and an optimum separation of 87 % is established. Based on the results obtained in this work it can be concluded that the model is a reasonable representation of the system and can be used to obtain the necessary process insights for further process development.